“EU SOU FRACO, EU SOU HOMEM, EU SOU CARNE” (NARRATIVAS E MASCULINIDADES NO DISCURSO) - Santos, William Soares Dos (Intercâmbio, 2010)
The aim of this paper is to show how hegemonic masculine identity orients the speech of a man in an research interview about his religious trajectory. The analysis was triggered from a socio-constucionist approach to discourse (Moita Lopes, 1996) which is linked to a socio-interactional perspective (Gumperz [1982], 2002; Goffman [1974] 2002) that considers social identity as multiple and fluxing. The characters and the emergent voices within the narratives (Labov, 1972), as well the narrator who is aligned with them, show how the identities of the referred men and women are shaped.